The Ecology and Etiology of Newly Emerging Marine Diseases 2001
DOI: 10.1007/978-94-017-3284-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Stony coral diseases observed in southwestern Caribbean reefs

Abstract: Thirteen reef areas of Colombian territories in the Southwestern Caribbean were surveyed during the last 10 years. Coral diseases have been recorded in all these areas since 1990 and some of them have increased progressively. Six types were differentiated in the region, of which black band disease (BBD), dark spots disease (DSD), white band disease (WBD) and white plague disease (WPD) are widespread and common. Yellow band disease (YBD) was observed only since April 1998 but has been found now in seven reef ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 2 publications
3
24
0
2
Order By: Relevance
“…White-plague (e.g., Dustan, 1977;Dustan & Halas, 1987;Richardson et al, 1998), bleaching, and dark spots ) were observed on several habitats throughout the banks. These diseases have been observed in these areas of Colombian reefs since the mid 1990s (see review in Garzon-Ferreira et al, 2001 and references therein). Effects from white plague were particularly serious in a localized but extensive area of Serrana Bank (Sánchez et al, submitted).…”
Section: Current State Of the Benthic Communitiesmentioning
confidence: 99%
“…White-plague (e.g., Dustan, 1977;Dustan & Halas, 1987;Richardson et al, 1998), bleaching, and dark spots ) were observed on several habitats throughout the banks. These diseases have been observed in these areas of Colombian reefs since the mid 1990s (see review in Garzon-Ferreira et al, 2001 and references therein). Effects from white plague were particularly serious in a localized but extensive area of Serrana Bank (Sánchez et al, submitted).…”
Section: Current State Of the Benthic Communitiesmentioning
confidence: 99%
“…4C,D) disease has been reported throughout the Caribbean since 1994 (Santavy & Peters 1997, Santavy et al 1999, Cervino et al 2001, Toller et al 2001, Weil et al 2002. YBL affects 9 scleractinian coral species (Table 2; Garzón-Ferreira et al 2001), but most often affects Montastraea annularis (Cervino et al 2001). The causal agent of YBL is unknown.…”
Section: Yellow Blotch/bandmentioning
confidence: 99%
“…An unequivocal sign of these changes is the loss of coral cover which was estimated around 5% per year until 2001 (Gardner et al 2003, Côté et al 2005. Multiple natural and anthropogenic disturbances such as coastal development (Hallock et al 1993, Bak & Nieuwland 1995, Guzman & Jackson 2008, bleaching events and hurricanes (Edmunds 2002, Buddemeier et al 2004, Somerfield et al 2008 and coral diseases (Aronson & Precht 1997, Garzón-Ferreira et al 2001, Sutherland et al 2004) among others have contributed to coral reductions. Algae have become more abundant on many reefs across the Caribbean as a result of coral mortality (McClanahan et al 1999 and reduced herbivory (Hughes 1994, Mumby et al 2006.…”
mentioning
confidence: 99%